ANALISIS KESULITAN BELAJAR PADA SISWA SEKOLAH DASAR DI SDN 11 PANDEGLANG - Mulyawan, Galuh; Maulia, Delia Ayunda; Prabowo, Arga Satrio; Nadirah, Yahdinil Firda (Journal of Professional Elementary Education, 2025)
Elementary education is a crucial initial stage in shaping students' cognitive, affective, and psychomotor abilities. However, in the learning process, not all students are able to follow the material optimally. Many elementary school students experience learning difficulties, such as difficulty understanding the material, low learning motivation, and unsatisfactory learning outcomes. These difficulties, if not identified and addressed early on, can have an impact on students' academic, social, and emotional development. This study aims to analyze the diagnosis of students' learning difficulties at SDN 11 Pandeglang based on five indicators, namely the ability to receive material, interest in learning, perseverance in learning, feelings while participating in learning, and learning outcomes. This study uses a descriptive quantitative approach with data collection techniques through questionnaires and observations. The subjects of the study were students of SDN 11 Pandeglang. Data were analyzed using descriptive statistical analysis techniques in the form of average scores and categorization. The results showed that most indicators of learning difficulties were in the moderate category, namely the ability to receive material (1.6), interest in learning (2.0), perseverance (2.25), and learning outcomes (2.12). Meanwhile, feelings during learning received the lowest score (1.3) and were included in the low category, indicating significant emotional barriers. This finding reinforces the importance of the role of teachers in recognizing and addressing students' learning difficulties comprehensively in order to create an effective, inclusive learning process that supports optimal student development.